Length‐weight relationships of Secutor interruptus (Valencennes, 1835) and Opisthopterus tardoore (Cuvier, 1829) from the South China Sea, Sarawak. (13th January 2018) - Kumar, U.; Rajaee, A. H.; Idris, M. H.; Nesarul, M. H.; Siddique, M. A. M.; Abu Hena, M. K.
Summary: Length–weight relationships for two fish species Secutor interruptus (Valencennes, 1835) (2.3–5.0 cm in size) and Opisthopterus tardoore (Cuvier, 1829) (9.2–15.6 cm in size) were determined. Samplings were conducted at Bintulu coast, South China Sea, Sarawak from September to October 2016 using a pull net having different mesh size from 6 inch at the mouth, 4 inch at the bag area, 2 inch at the panel and 1.5 inch at the cod end. The estimated growth coefficient ( b ) was 2.96 for S. interruptus and 3.11 for O. tardoore . No information regarding length‐weight relationships was reported previously in FishBase for either S. interruptus or O. tardoore .